Research on Key Technologies of Temperature Rise Suppression for Motor Grease Lubricated Rolling Bearing - Baoying SHE; Sizhou GUO; Ronghai MEI; Haijiang LI; Jiawei CAO (机车电传动)
At present, grease lubrication is widely used in motor rolling bearings. However, the bearing DN value increases rapidly with the increasing of motor speed and power for the factor that the lubricating grease is semi-solid with poor flow and heat dissipation ability. Thus, the key problem of utilizing grease lubrication in bearing is how to control the temperature rise of bearings. The relationship between the flow law of grease in rolling bearings and the temperature rise of bearings was explained. Moreover, the effective control strategy for temperature rise of grease-lubricated rolling bearings was proposed from the aspects of bearing clearance, type and filling amount of grease, lubrication sealing configuration and running-in mode.